Maleic anhydride polyethylene octene elastomer toughened polyamide 6/polypropylene nanocomposites: mechanical and morphological properties - Hassan, Azman; Othman, N.; Wahit, Mat Uzir; Lim, J. W.; Rahmat, A. R.; Mohd. Ishak, Z. A. (2005)

(untitled)
A series of polyamide 6 / polypropylene (PA6/PP) blends containing 4 wt% of organophilic modified montmorillonite (MET) were designed and prepared by melt compounding followed by injection moulding. Maleic anhydride polyethylene octene elastomer (POE-g-MA) was used as impact modifier as well as compatibilizer in the blend system. Three weight ratios of PA6/PP blends were prepared i.e. 80/20, 70/30, and 60/40. The mechanical properties of PA6/PP blends and nanocomposite were studied through flexural and impact properties. Scanning electron microscopy (SEM) was used to study the microstructure. The incorporation of 10wt% POE-g-MA into PA6/PP blends significantly increased the toughness with a corresponding reduction in strength and stiffness. However, on further addition of 4 wt% organoclay, the strength and modulus increased but with a sacrifice in impact strength. It was also found that the mechanical properties area function of blend properties. Interesting, 70/30 PA6/PP blend ratio has the optimum impact strength values for both blends and nanocomposites. The morphological study revealed that POE-g particles were finely dispersed in the PA6 dominant blends system.